Colorado water, July/August 2015 - Middleton, Lindsey A., editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2015)
Newsletter of the Water Center of Colorado State University. Theme: Colorado Water Institute: fifty years: research, education, outreach.
The newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the state's research universities.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado